2016
DOI: 10.1007/s00439-016-1636-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of complex diseases by common genetic markers: state of the art and further perspectives

Abstract: Reliable risk assessment of frequent, but treatable diseases and disorders has considerable clinical and socio-economic relevance. However, as these conditions usually originate from a complex interplay between genetic and environmental factors, precise prediction remains a considerable challenge. The current progress in genotyping technology has resulted in a substantial increase of knowledge regarding the genetic basis of such diseases and disorders. Consequently, common genetic risk variants are increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 92 publications
0
22
0
1
Order By: Relevance
“…Firstly, our study established a risk prediction model through screening and evaluating genetic susceptibility from previous studies that have high prediction accuracy. Furthermore, genetic variants have several advantages as predictors, including remaining unchanged, predictable life-long risk and easy, accurate and cost-effective measurement [14,37]. In addition, the combining of genetic and clinical factors into one model was feasible in clinical practice for trauma patients, which might enhance the discrimination of patients at high risk for sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our study established a risk prediction model through screening and evaluating genetic susceptibility from previous studies that have high prediction accuracy. Furthermore, genetic variants have several advantages as predictors, including remaining unchanged, predictable life-long risk and easy, accurate and cost-effective measurement [14,37]. In addition, the combining of genetic and clinical factors into one model was feasible in clinical practice for trauma patients, which might enhance the discrimination of patients at high risk for sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not replicate these results in a second cohort, the LOOCV statistical approach is able to minimize this limitation. Indeed, one recent review showed that, among 55 prediction studies, nine used cross-validation approach as independent validation, and only six validated in a second cohort [41]. In addition, it would be interesting to know whether specific SNPs may be associated with AED response for different drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed an improvement of discriminatory accuracy when combining clinical variables with SNP information [41], including breast cancer(from 0.58 to 0.61) [42], nasopharyngeal carcinoma (from 0.68 to 0.74) [43], and venous thrombosis (from 0.77 to 0.82)[44]. In our study, we demonstrate that by including SNP information in addition to only clinical and imaging parameters, there was a significant increase in the discriminatory accuracy from 0.4568 to 0.8177.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prediction due to the addition of the PRS between good and poor readers was analyzed using different measures of reclassification (IDI and continuous NRI) applying the R add‐on package PredictABEL 1.2‐2 (Kundu, Aulchenko, & Janssens, 2014). Reclassification measures indicate if classification of cases and controls improves when adding new information (e.g., genetics) to the model (Müller et al., 2016). …”
Section: Methodsmentioning
confidence: 99%